Peranan Pemerintah Daerah dalam Melakukan Pengawasan Tenaga Kerja Asing - Johanes O. Amboki (Kyadiren, 2022)
The current study is aimed to investigate the role of local governments, especially The Legal Department in evaluating and supervising foreign workers. This supervision is important because foreign workers who do not have official permits and documents can have an impact on the region. In this study, it is described that regional supervision has not been fully provided. This is due to the provisions of Law No. 23/2014 concerning Regional Government and The Minister of Manpower No. 10/2018 concerning Procedures for the Use of Foreign Workers which does not fully regulate the involvement of local governments in supervising foreign workers